2007
DOI: 10.1007/s00441-007-0443-1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of spicule production in the marine sponge Hymeniacidon perlevis during in vitro cell culture and seasonal development in the field

Abstract: To characterize the formation of silica spicules, the dynamics of spiculogenesis of an intertidal marine sponge Hymeniacidon perlevis (Montagu 1818) (Porifera: Demospongiae) were investigated by measuring the gene expression of silicatein (the enzyme responsible for spicule silicification) and the dimensional changes of spicules during the developmental process of individual sponges and in cell cultures of primmorphs of archaeocyte-dominant cell populations. The different developmental stages of spicules were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 32 publications
2
28
1
Order By: Relevance
“…This finding suggests that silicatein expression is not directly connected with number of spicules, although it should be recognised that these silicatein genes are expressed at high levels before the start of spicule formation. This delay seen in the early stages between silicatein expression and spicule number can be expected as spiculogenesis requires multiple steps before the initial silica deposition, including translation, phosphorylation and self-assembly (Cao et al 2007). This will confound the correlation of expression with spicule number, in addition to the variability observed in both data throughout development.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This finding suggests that silicatein expression is not directly connected with number of spicules, although it should be recognised that these silicatein genes are expressed at high levels before the start of spicule formation. This delay seen in the early stages between silicatein expression and spicule number can be expected as spiculogenesis requires multiple steps before the initial silica deposition, including translation, phosphorylation and self-assembly (Cao et al 2007). This will confound the correlation of expression with spicule number, in addition to the variability observed in both data throughout development.…”
Section: Discussionmentioning
confidence: 99%
“…3.7). In Hymeniacidon perlevis, it was shown that silicatein expression changed depending on the sampling part of the individual, front, middle or back; each part affected by different micro-environment like water current flow capacity, higher flow resulted in higher expression (Cao et al 2007). Larvae in this study were from a pool of adult sponges collected in different parts of the reef.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations